2020
DOI: 10.1108/jcm-09-2017-2373
|View full text |Cite
|
Sign up to set email alerts
|

Exploring IKEA effect in self-expressive mass customization: underlying mechanism and boundary conditions

Abstract: Purpose This study aims to understand the underlying mechanism and boundary conditions of the IKEA effect in self-expressive mass customization (MC). It examines the effect of the extent of choice in MC toolkits in terms of perceived value of self-designed products, as well as how self-expression mediates this effect and what kind of consumers are more inclined to experience such effect. Design/methodology/approach Two experiments were conducted, using online MC toolkits. In total, 393 consumers participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…By comparison with the spectrum of acr-rGO, the characteristic peak of C=C (in DOPO/Acr-rGO) disappeared at 1623 cm −1 . Several new characteristic peaks were observed: 913 cm −1 (P-O-phenyl), 1245 cm −1 (P=O), 1429 cm −1 (P-phenyl), 1581 cm −1 (phenyl), 1595 cm −1 and 1608 cm −1 (Ma et al, 2018;Lin et al, 2020). From the FTIR analysis, it was evident that m-rGO was successfully synthesized.…”
Section: Structural Characterization Of Surface Modified Reduced Grap...mentioning
confidence: 90%
See 1 more Smart Citation
“…By comparison with the spectrum of acr-rGO, the characteristic peak of C=C (in DOPO/Acr-rGO) disappeared at 1623 cm −1 . Several new characteristic peaks were observed: 913 cm −1 (P-O-phenyl), 1245 cm −1 (P=O), 1429 cm −1 (P-phenyl), 1581 cm −1 (phenyl), 1595 cm −1 and 1608 cm −1 (Ma et al, 2018;Lin et al, 2020). From the FTIR analysis, it was evident that m-rGO was successfully synthesized.…”
Section: Structural Characterization Of Surface Modified Reduced Grap...mentioning
confidence: 90%
“…The IKEA effect Norton et al (2012) refer the definition of the IKEA effect as the increase in valuation of self-made products. More specifically, the IKEA effect was seen when individuals who build IKEA boxes, folded origami animals, and built objects from a set of Legos (as a part of Norton's experiment) were willing to pay more for their finished product than the same product that was assembled by an expert (Ling et al, 2020). According to Kim (2015) the specific strategy (IKEA effect), while enjoying a marketing effect, has become an opportunity for promoting transformation to a practical customer-oriented, differentiated furniture image solely for IKEA.…”
Section: 1mentioning
confidence: 99%
“…Second, Shmueli et al ( 2012 ) found that the IKEA effect increases product valuations depending on the difficulty of the assembly process. Third, Ling et al ( 2020 ) showed that the IKEA effect is magnified by increasing consumer choice opportunities in product completion. Gibbs and Drolet ( 2003 ) found that consumers' energy levels increase the likelihood of selecting DIY products.…”
Section: Discussionmentioning
confidence: 99%
“…(Kwon et al, 2017) Online self-customisation allows customers to identify themselves with products. (Ling et al, 2020) Customisation leads to better product assessments. Product attributes (Chiou & Ting, 2011) Utilitarian products are instrumental and functional, while hedonic ones provide fun and pleasure.…”
Section: Research Focusmentioning
confidence: 99%